RANCANG BANGUN SISTEM INFORMASI JASA DAN PENJUALAN BERBASIS WEBSITE PADA SALON DYNA - Lestariana, Dorani; Arnomo, Sasa (LPPM Universitas Putera Batam, 2022)
Abstract Web-Based Service and Sales Information System at Salon Dina can facilitate the sales process at Salon Dina. With the existence of a web-based service and sales information system at the dina salon, it can improve the quality of service and data management at the dina salon. In addition, the salon can easily process sales data, goods data, purchase data and user data stored in the database. In this study, the author discusses how to design and build a Service and Sales Information System at Salon Dina. The system development methodology used is the System Development Life Cycle (SDLC) waterfall model which includes the stages of needs analysis, system design, system implementation and system testing. This system is built using the Hypertext Preprocessor (PHP) programming language, the framework uses CodeIgniter and the database server uses MySQL. The results to be achieved in this study are, Service and Sales Information Systems at Salon Dina. With the construction of this system, it is hoped that it can help the salon in processing sales data, goods data, purchase data and user data to be more effective and structured. Keywords: Sales, Information Systems, System Development Life Cycle (SDLC), Web